Topic identification and content analysis of internet medical policies under the background of Healthy China 2030 - Guoping Wu; Hao Ning; Youshu Yuan; Junbai Chen; Guoxiang Li; Shuang Liu; Zhiwei Wang (BMC, 2024)
Abstract Objective This study aims to analyse the content of internet medical policies, grasp the inherent laws of the development of internet medical policies and provide references for improving the policy system. Methods On the basis of web crawler technology, 436 internet medical policies issued by the central and local governments after the Healthy China Strategy was proposed were collected. The BERTopic model was used to extract topics, and a comprehensive analysis of China's internet medical policy texts was conducted through the analysis of topic content, topic hierarchy and topic clusters. Results A total of 27 topics were identified in China's internet medical policies, mainly focussing on five topic clusters: medical service regulation, elderly nursing and children's healthcare using traditional Chinese medicine, user safety guarantees, health education and communication and infectious disease treatment and recovery guidance. Conclusions Different topic contents play a role in promoting the comprehensive and standardized development of internet medical services. However, there is still room for further improvement in policy integrity, consideration of multiple types of users, and implementation effectiveness. Continuous efforts are needed to optimize the effectiveness of policies.